The Association Between Gait Speed and Sleep Problems Among Chinese Adults Aged 50 and Greater - Wang, Lili; Zou, Benxu (Frontiers in Neuroscience, 2022)
Objective: Although many studies have examined the relationship between sleep problems and physical function, few have examined the relationship between sleep problems and walking speed. The present cross-sectional study was to investigate the association between sleep quality and sleep duration and gait speed in Chinese adults. Methods: 13,367 participants were recruited in this cross-sectional study, retrieving the data from the Global Ageing and Adult Health Survey (SAGE). Gait speed was measured using the 4-meter walking test. sleep problems were measured using the sleep quality and sleep duration. Multivariate logistic regression model was used to examine the association between sleep problems and gait speed. Results: In the adjusted model, poor sleep quality and longer sleep duration were significantly associated with slower normal walking speed in Chinese adults (p<0.001). and slower rapid gait speed was significantly associated with longer sleep duration (p<0.001). Moreover, there were negatively significant associations between normal gait speed and sleep quality in male adults (p<0.01). Conclusion: The findings suggest that slower walking speed may predict the poor sleep quality in Chinese adults.